Art: a conversation partner in theological education - Mallaby, Anne (Practical theology, 2019)
This article explores the role of art as a source for theological reflection. Art extends an invitation for viewers to discover connections between their experiences and their frameworks for interpreting reality and meaning. This examination draws on Tim Gorringe's argument that art offers a secular parable with a three-fold function: (i) leaning into an eschatological view of an alternative future; (ii) inviting a vision of shalom that contributes to a greater good; and (iii) inviting viewers to attend to what is, and, therefore, to see more deeply. This engagement with art stimulates theological conversation toward insight as viewers ponder their responses and integrate their experiences with their meaning-making frameworks. In this way, art provides a significant resource for ministry and an invaluable source for reflection within the theological endeavour.